Utilization of rice straw as a paper / Muhammad Imaduddin Mat Zaid, Muhammad Hafizul Hisyam Ahmad and Wan Tabadrul Hisyam Wan Ahmad - Mat Zaid, Muhammad Imaduddin; Ahmad, Muhammad Hafizul Hisyam; Wan Ahmad, Wan Tabadrul Hisyam (Faculty of Plantation and Agrotechnology, 2023)
Every year, the rice harvest season is followed by raging fires in rice growing areas. This is because farmers burn unwanted straw in the open which will cause air pollution. Unbeknownst to them, rice straw is one of the most important materials that have been used for pulp and paper production because of its abundance and cost effectiveness. In relation to that, the process of converting rice straw to paper is an initiative to overcome the problem with the removed rice straw being mixed with used paper to make recycled paper with acceptable properties. Develop sustainable processing technology that can convert agricultural waste such as rice straw into pulp. The soda pulp manufacturing process was carried out to remove lignin. This process was designed to measure the effects of sodium hydroxide concentration and temperature on cellulose and lignin content of rice straw, and tensile strength and water absorption. Using NaOH concentration (4-10% w/w) and temperature (60-9 0C) for 1 hour with a ratio between rice straw and used paper (1:1-1:9) with NaOH concentration 8% and temperature 90°C. The result of this is the highest total cellulose content and tensile strength and the lowest total lignin content and water absorption.